Using Dialectics to Build Leader-Stakeholder Relationships: An Exploratory Study on Relational Dialectics in Chinese Corporate Leaders' Web-Based Messages. (January 2018) - Ngai, Cindy Sing-Bik; Singh, Rita Gill
In large Chinese corporations operating in the Greater China region, there is an increasing use of web-based bilingual messages by their corporate leaders for fostering relationships with stakeholders. Although frequently presented as literal translations of each other, leaders' bilingual communication sometimes tends to exhibit nonliteral variations. This study aims to examine the relational dialectics theory in the construction of leader-stakeholder relationships in leaders' bilingual web-based messages and explores the dialectical oppositions that are embedded in the Chinese and English versions of these messages. The results suggest that leaders' communication is characterized by the deliberate use of different dialectics that allow them to tailor their communication to the perceived needs of stakeholders from diverse linguistic and cultural backgrounds. In particular, the Chinese version of the message is adapted to exude greater connection, openness, affection, and predictability in content as well as style, which is believed to strengthen relationships with stakeholders.